Ethics in the Curriculum: A Study of Ethical Frameworks and Moral Imperatives Embedded in Adult Education Graduate Programs - Thomas J. Sork (Adult Education Research Conference, 2001)
This study concerns the ways in which programs designed to prepare adult educators for practice represent moral imperatives and ethical frameworks in the curriculum. Preliminary findings support the central role of social and political context and personal biography of faculty in determining which imperatives and frameworks are reflected in the curriculum.